Evaluation of Early Adolescent Subjective Well-Being in Terms of Submissive Behavior and Self-Esteem. Issue 45 (8th August 2019) - Odacı, Hatice; Kınık, Özge
Abstract: This research aimed to investigate the correlation between subjective well-being and submissive behavior and self-esteem in students in the early adolescent period. The research was completed with a relational design. The research group comprised sixth, seventh, and eighth class middle school students in the spring term of the 2015–2016 academic year in Trabzon province. Data collection tools included a Personal Information Form, Submissive Behavior Scale, Two-Dimensional Self-Respect Scale (Self-Liking and Self-Confidence Scale), Satisfaction with Life Scale and Positive and Negative Affect Schedule. The results of the correlation analysis found a significant positive correlation between subjective well-being and self-esteem ( r  = 0.54, p  < 0.01; 95% CI [0.44, 0.61], Cohen's d  = 1.28); however, the correlation between subjective well-being and submissive behavior was not significant ( r  = –0.02, p  > 0.05; 95% CI [–0.11, 0.09], Cohen's d  = 0.04). There was a significant negative correlation identified between self-esteem and submissive behavior ( r  = –0.10, p < 0.05; 95% CI [–0.20, –0.01], Cohen's d  = –0.20). Additionally, according to our findings, self-esteem accounts for 29% of the variation in well-being ( F (1, 367) = 150.79, p  < 0.001). The contribution of self-esteem to the subjective well-being explanatory model was found to be significant ( sz  = 0.54, p  < 0.001).